Identification of meteorological drought year for Varanasi district U.P. - Meshram, Sumeet; Kant, Shri; Sahu, K C (Recent Research in Science and Technology, 2014)
Drought can be defined as a temporary harmful and widespread lack of available water with respect to specific need. It implies a deficiency of rainfall of sufficient magnitude over a prolonged duration so as to interfere with some phases of regional economic activities. According to the India Meteorological Department (IMD) an area is considered to be drought if it receives seasonal total rainfall less than 75% of its normal value. The rainfall records of 37 years for Varanasi were obtained from the India Meteorological department (IMD). Rainfall data has been subjected to various kind of analysis including seasonal & annual rainfall departures, probability distribution and dry spell analysis etc. For identification of drought years and the extent of deficit of annual rainfall, the annual rainfall departure analysis has been carried out. A year is considered as drought year if the total amount of annual rainfall over an area is deficient by more than 25% of its normal value. From the analysis it is observed that in years 1972, 1979, 1992, 2004 as moderate drought years occurred in Varanasi district & there were no severe drought in this region. The chance of occurrence of drought in every 10 years varies from 1 to 2. It means that year after every 4 to 5 is a drought year.